Resistência à fratura de diferentes núcleos de preenchimento com compósitos bulk fill em dentes com extensa destruição coronária - Oliveira, Carlos Rangel de Moura (2019)
This study aimed to evaluate the ultimate fracture strength and failure modes of different core techniques associated with intraradicular fiberpost in bovine mandibular lateral incisors with extensive coronary destruction. Forty teeth were prepared endodontically, randomly divided into 4 experimental groups (n=10) and a fiberpost (Whitepost DC0.5) was cemented with LuxaCore Z for all groups. The core was confeccioned, after obtaining a 1.0 mm cervical ferrule, with: FOBF-Filtek One Bulk Fill; FZ350- Filtek Z350 XT; FBFF-Filtek Bulk Fill Flow; and LCZ-LuxaCore Z. Total zirconia crowns (Y-TZP) produced by CAD/CAM were cemented with RelyX U200. After storage in distilled water at 37ºC for 48 h, the specimens were submitted to thermal cycling (10,000 cycles, 5- 55ºC, 30 s dwell time) and, afterwards, to the mechanical test of compressive strength fracture (1.0 mm / min) at 135º along the tooth axis in electromechanical machine (EMIC DL2000). The ultimate load supported by each specimen was recorded in Newton. The fracture mode was classified by means of stereomicroscopic loupe analysis (30X). The fracture strength data were analyzed by the non-parametric Kruskal-Wallis test, followed by the post-hoc Dunn test. The data of the fracture modes were analyzed by Fisher's exact test (α=0.05). No significant differences (p>0.05) were observed among the FOBF, FZ350 and FBFF groups (mean ranks= 20.30, 12.20 and 23.20, respectively). LCZ (mean rank= 26.30) produced similar results to those of FOBF and FBFF (p>0.05) and higher than those of FZ350 (p=0.042). The most frequent type of failure was irreparable, regardless of the experimental condition. The lowest percentages of reparable fractures were 10% for the FOBF group, followed by 20% of LCZ. The use of bulk fill materials, including the “core-and-post” LCZ composite, did not impair the ultimate fracture strength of endodontically treated teeth with extensive coronal destruction. The use LCZ made it possible to perform the procedures in fewer steps and less clinical time, without impairing the fracture resistance of endodontically treated lateral incisors.